2010
DOI: 10.1007/s11998-010-9297-7
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of ultrasonication time on transport properties of polyurethane/organoclay nanocomposite coatings

Abstract: In this study, a series of polyurethane (PU)/ organically modified montmorillonite (OMMT) clay nanocomposites were synthesized by in situ polymerization technique through an ultrasonication-assisted process at various processing times. Wide angle X-ray diffraction (WAXD) was employed to investigate the effect of processing time on degree of delamination of clay platelets. In order to evaluate the effect of ultrasonication time on transport properties of the PU/OMMT composites, diffusion coefficient and maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The sonication assisted in breaking the clay aggregate [51] into dispersed clay particles. High shear homogenization is beneficial for dispersing the clay platelets homogeneously [52] throughout the polymer matrix.…”
Section: Mechanical Properties Of Copus-c30b Nanocomposites Filmmentioning
confidence: 99%
“…The sonication assisted in breaking the clay aggregate [51] into dispersed clay particles. High shear homogenization is beneficial for dispersing the clay platelets homogeneously [52] throughout the polymer matrix.…”
Section: Mechanical Properties Of Copus-c30b Nanocomposites Filmmentioning
confidence: 99%
“…The R p value for the LPP/ZnO-0.06 coated CS showed a very high (4.46 Â 10 5 kU, 1.58 Â 10 2 kU) increase with respect to the LPP coated CS (68.94 kU, 18.53 kU) in 3.5 wt% NaCl and 3.5 wt% HCl, respectively. 18,77 The hydrophobic character of the virgin coatings increases with the incorporation of ZnO NP (as discussed in previous section), which do not allow wetting of the surface that inhibits penetration of corrosive ions. These results demonstrate the ability of the nanocomposite coatings to inhibit the corrosion process by blocking Scheme 5 The mechanism occurring at the -COOH end of LPP.…”
Section: Hydrophobicitymentioning
confidence: 99%
“…The overall underlying idea is to harness nature's abundant sustainable resources, by combination of the "green" characteristics of biopolymers and the high performance rendered by nanomaterials for advanced functional applications such as drug delivery, medicine, sensing devices, ame retardancy, food packaging, gasdiffusion barriers, protective coatings and others. The inclusion of such nanoparticles overcomes some drawbacks of plant oil derivatives such as poor load bearing ability, hardness, inadequate rigidity and strength, 2,11,13 and improves the antimicrobial behavior, [14][15][16] thermal stability, 7,11,16 corrosion protection performance 17,18 and other properties, in nal BNCs thus broadening their areas of applications. Their derivatives such as alkyds, polyesteramides, polyurethanes [PU] and others nd applications as biodiesel, printing inks, lubricants, adhesives, coatings and paints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High aspect ratio of nanoclay was proved to improve the barrier properties [13][14][15], because it might attribute the reduction in straightway movement of water vapor and oxygen molecule, which results in increasing the effective paths for diffusion of each molecule [16]. Several reports have shown that the dispersion of nanoclay and the morphology of the nanocomposite depend on various factors, such as the mixing method [17], mixing speed [18], and clay content [19].…”
Section: Introductionmentioning
confidence: 99%